2007
DOI: 10.1073/pnas.0703790104
|View full text |Cite
|
Sign up to set email alerts
|

Herpes simplex virus glycoproteins gB and gH function in fusion between the virion envelope and the outer nuclear membrane

Abstract: Herpesviruses must traverse the nuclear envelope to gain access to the cytoplasm and, ultimately, to exit cells. It is believed that herpesvirus nucleocapsids enter the perinuclear space by budding through the inner nuclear membrane (NM). To reach the cytoplasm these enveloped particles must fuse with the outer NM and the unenveloped capsids then acquire a second envelope in the transGolgi network. Little is known about the process by which herpesviruses virions fuse with the outer NM. Here we show that a herp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
201
3

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 165 publications
(221 citation statements)
references
References 38 publications
17
201
3
Order By: Relevance
“…At that stage, gM could regulate membrane fusion, perhaps preventing the unrestricted fusion of the inner and outer nuclear membrane at a time when new viral particles have yet to be assembled. The targeting of gM to nuclear membranes prior to the presence of the gB, gD, and gH fusogenic machinery would be consistent with such a concept (38,(50)(51)(52)(53). As gM is subsequently detected on perinuclear virions at 14 hpi (39), it could then promote the fusion of the enveloped viral particles with the outer nuclear membrane, although data by Leege and colleagues argue otherwise, as the deletion of gM from the related pseudorabies virus does not lead to an accumulation of perinuclear virions (17).…”
Section: Discussionsupporting
confidence: 50%
“…At that stage, gM could regulate membrane fusion, perhaps preventing the unrestricted fusion of the inner and outer nuclear membrane at a time when new viral particles have yet to be assembled. The targeting of gM to nuclear membranes prior to the presence of the gB, gD, and gH fusogenic machinery would be consistent with such a concept (38,(50)(51)(52)(53). As gM is subsequently detected on perinuclear virions at 14 hpi (39), it could then promote the fusion of the enveloped viral particles with the outer nuclear membrane, although data by Leege and colleagues argue otherwise, as the deletion of gM from the related pseudorabies virus does not lead to an accumulation of perinuclear virions (17).…”
Section: Discussionsupporting
confidence: 50%
“…Our data also were not in agreement with a previous report that pseudorabies virus (PRV) UL47 was not present in primary enveloped virions (40). It appears that, despite their genetic similarities, HSV-1 and PRV differ in the compositions of their virions since HSV-1 primary enveloped virions contain gB, gD, gH/gL, gM, VP22, VHS, VP16, and UL11, but PRV does not (1,37,38,(41)(42)(43)(44)(45). Alternatively, UL47 may have been present in PRV primary enveloped virions but could not be detected with the antibody used in that study.…”
Section: Figcontrasting
confidence: 47%
“…Recently, a receptor for gB was described (23). Of note, although for virus-to-cell entry and for cell-cell fusion, fusion requires the simultaneous presence of gB and gH/gL, fusion of perinuclear virions with the outer nuclear membranes appears to necessitate either gH/gL or gB (24). Furthermore, it has been reported that HSV fusion may be preceded by a hemifusion intermediate mediated by gD and gH/gL (25).…”
Section: Herpes Simplex Virus (Hsv)mentioning
confidence: 99%